FENOMENA RENDAHNYA MINAT BELAJAR SISWA DALAM PEMBELAJARAN PAI : TANTANGAN DAN UPAYA MAHASISWA PPK DI SEKOLAH - Lusi Susanti; Muhamad Syahril Sidik; Muhammad Rifqi Romli; Hanipah; Muhammad Rizkillahi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student attendance constitutes a fundamental indicator of instructional continuity and character development in madrasah education. Irregular and low attendance rates remain evident at Madrasah Aliyah Al-Muhdi, thus requiring systematic educational interventions through the involvement of teachers and parents. This study aims to analyze the initial condition of student attendance, the implementation of the home visit program, the forms of teachers’ personal approaches, and the effectiveness of these strategies in improving student attendance during the Teaching Practice (PPK) program. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing with source and technique triangulation. The findings indicate that the home visit program strengthened school–family partnerships and increased parental involvement in supervising students’ learning. Teachers’ personal approaches, implemented through guidance, individualized mentoring, and interpersonal communication, improved students’ motivation and disciplinary awareness. The implementation of both strategies proved effective in significantly increasing and regularizing student attendance. Therefore, the home visit program and teachers’ personal approaches represent effective pedagogical strategies for improving student attendance in madrasah education.